Адаптація інструментарію внутрішнього маркетингу до системи управління підприємством - Сагайдак, М.П. (Культура народов Причерноморья, 2013)
У статті проаналізовано підходи вітчизняних та закордонних науковців до проблем
управління підприємством та взаємовідносинами зі стейкхолдерами крізь призму формування системи
внутрішнього маркетингу і використання його інструментарію. З використанням інструментарію
внутрішнього маркетингу запропоновано здійснення дослідження рівня задоволеності й залучення
персоналу до процесу управління підприємством. Надано рекомендації щодо практичного застосування
інструментарію внутрішнього маркетингу у підвищенні продуктивності підприємства і персоналу. В статье проанализированы подходы отечественных и зарубежных ученых к проблемам
управления предприятием и взаимоотношениями со стейкхолдерами сквозь призму формирования
системы внутреннего маркетинга и использования его инструментария. С использованием
инструментария внутреннего маркетинга предложено проведение исследования уровня
удовлетворенности и вовлеченности персонала в процесс управления предприятием. Даны рекомендации
по практическому применению инструментария внутреннего маркетинга в повышении
производительности предприятия и персонала. Domestic and foreign scientists approaches to the enterprise management issues, relationship with
stakeholders, internal marketing system formation and effective use of its tools were analyzed in the article.
Main premises for introducing the internal marketing concept into the service industries activity were defined:
organizational structure, effective recruiting, the possibility of human resources implementation, corporate
identity management. Main purpose of internal marketing was found out, it consists in highly attractive image of
the enterprise- employer creating, it allows employee, except material component, fully implement professional
competence and personal qualities.
Using internal marketing tools, research of satisfaction level and staff involvement into the enterprise
management process was conducted. It is proved, that employee motivational profile study allows to track
relation of unit employees work satisfaction with work satisfaction of employees in general, and the difference
between their levels illustrates presence or absence of unused motivation potential of specific unit employees.
The recommendations on the practical application of internal marketing tools for increasing company and staff
productivity were given.